Literature Reviews on the Challenges and Opportunities of ESG Integration in Investment Decisions - Ilen Marliani (Citakonsultindo, 2024)
The integration of Environmental, Social, and Governance (ESG) in investment decisions is becoming an important subject in the world of modern finance. This research explores the challenges and opportunities associated with the integration of ESG in investment decision-making. With a qualitative approach using literature review methods, this research explores various aspects that influence sustainable investment decision-making. The results of the analysis show that although there are great opportunities to improve long-term investment performance through ESG integration, there are still several challenges that need to be overcome. These challenges include a lack of transparency, reliability, consistency, and materiality in reporting ESG data, as well as difficulties in applying accounting controls to ESG data, which is often qualitative and prospective.